The Association between Myocardial Perfusion Scan and Electrocardiographic Findings among Patients with Myocardial Ischemia - Behzad Farahani; Ramin Skandari; Mohammad Amin Abbasi; Sepideh Aghalou; Sepehr Gohari; Amir Hossein Heydari; Mehrdad Farahani (International Journal of Cardiovascular Practice, 2017)
Introduction: The aim of this study was to determine the consistency of Electrocardiography (ECG) and myocardial perfusion scan findings of patients with myocardial ischemia at Firoozgar and Hazrat-Rasool hospitals.Methods: Electrocardiogram of 80 patients undergoing myocardial perfusion scans was analyzed. All patients had a stable angina. All patients with bundle branch blocks and history of MI and coronary bypass or angiography were excluded. Overall, 120 patients were evaluated with single photon emission tomography/myocardial perfusion imaging for ischemia and 80 patients had a positive test.Results: Forty-five percent of patients were female and 55% were male. The average age of patients was 61.48 years. Sixty-one patients (76.25%) had normal ECG and 19 patients (23.75) had pathological changes in their ECG. Eleven patients had ST segment depression and 6 patients had T wave inversion. Furthermore, 21 patients (26.25%) had lateral wall ischemia in their myocardial perfusion scan and 13 (16.25%) patients had septal wall ischemia. The ECG changes in male patients and hypertensive cases were more prominent.Conclusions: This study showed that ST-T changes (ST depression and T inversion) in the ECG are more suggestive of accuracy of myocardial ischemia and ECG.